Implementasi Algoritma Multi Group Huffman Untuk Kompresi File Video - Nurjanah, Nisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Technology is developing very rapidly along with the needs of society in obtaining information quickly. Information and communication technology has become an important part in processing data. Activities that were once manual, can now be processed using a computer so that it can save time and the resulting level of accuracy is much higher. One example of using a computer is processing video file data, this video file has a size large enough to require large storage media, for that data compression is very important because it reduces data storage requirements, speeding up data transmission. So the author developed a new system as an alternative with the help of a computer that has been equipped with the system. The author also uses Microsoft Visual Studio 2010 programming as a data processor in the compression process. In the research, the implementation process was carried out using this method for the video file compression process, this method will also help alleviate the challenges of using video files when storing or distributing in large capacities, this of course will greatly burden the computer in memory capacity, even when distribution becomes difficult. very slow and ineffective.